Implementasi Metode Picture and Picture untuk Meningkatkan Daya Ingat Siswa dalam Pembelajaran Bahasa Arab di SD IT Buah Hati Padang - Batubara, Aisyah Nur; Alfurqan, Alfurqan (Darul Yasin Al Sys, 2024)
This study aims to find out how the planning, implementation, eval_uation, supporting factors and inhibitions of the picture and picture method in Arabic lessons class V C. The picture and picture method is a method that uses picture or visual media, so that students are more interested and more enthusiastic in learning. The method used in this study is a qualitative method of field research. The data sources in this study consisted of one principal, one Arabic teacher and six students of class V C. The techniques used in data collection were observation, interviews, and documentation. The results of this study show that teachers have carried out planning by making teaching modules, implementation starts from opening, core and closing activities, and eval_uation. The results of the summative eval_uation of students stated that the quality of student learning using the picture and picture method was quite good.